2022-RA-1189-ESGO Challenges for a new robotic surgery program in gynaecological oncology at a cancer center in the United Kingdom during COVID-19 pandemic. (20th October 2022) - Abdelbar, Ahmed; Nikolopoulos, Manolis; Bakhoum, Tamer; Westbury, Emma; Mehra, Gautam
Abstract : Introduction/Background: The COVID-19 pandemic (CP) has resulted in a significant reduction of elective surgeries. Cancer treatment continued whilst adopting COVID-19 free pathways. Robotic surgery (RS) program was faced with numerous challenges. We outline the challenges that we faced at Guy's & St Thomas' (GSTT) hospital during the CP. Methodology: GSTT was among a few centers in the UK introducing RS training during CP. In December 2020, one surgeon started the RS training. The second surgeon followed after the completion of first 50 cases. The training included simulator training, dry-lab that focused on docking, undocking, and handling of instruments, and wet-lab surgical training. A local Proctor supported the surgeon in his first 10 surgeries until they gained independent competence. Online video library was used to familiarize the surgeon with this technology. We searched our database for the total and monthly numbers of RS between December 2020 and April 2022 and COVID-19 infections (CI) amongst patients. Results: There was no delay in the simulation training. Wet lab training was delayed due to temporary center closure. The surgeon's learning curve was slower at the beginning of the program. This was attributed to the lower influx of patients as a result of prioritization, lesser operative sessions, and delays in the mandatory training completion. 41 RS procedures were done in the first 8 month following a COVID-19 free pathway and were operated in an elective surgery hub with no visitors allowed. There were no cancellations due to CI during this period. Following the return to NHS hospital, 102 patients underwent RS in the subsequent 8 months. Preoperative isolation was gradually reduced then cancelled. One patient had a CI and was rescheduled accordingly. Conclusion: Covid pandemic has impacted the learning curve for RS with significant improvement noted after the gradual release of Covid related restrictions.